Primary Clear Cell Microcystic Adenoma of the Sinonasal Cavity: Pathological or Fortuitous Association?. (5th February 2017) - Cooper, Rosalin; Markham, Hannah; Theaker, Jeffery; Bateman, Adrian; Bunyan, David; Sommerlad, Matthew; Crawford, Gillian; Eccles, Diana
Abstract : Primary clear cell microcystic adenoma of the sinonasal cavity is rare. It has previously been described only as a VHL-associated tumour. Von Hippel-Lindau (VHL) syndrome is an inherited cancer syndrome characterised by an elevated risk of neoplasia including clear cell renal cell carcinoma (ccRCC), haemangioblastoma, and phaeochromocytoma. We describe the second reported case of a primary clear cell microcystic adenoma of the sinonasal cavity. The 39-year-old patient with VHL syndrome had previously undergone resection and ablation of ccRCC. He presented with epistaxis. Imaging demonstrated a mass in the ethmoid sinus. Initial clinical suspicion was of metastatic ccRCC. However, tumour morphology and immunoprofile were distinct from the previous ccRCC and supported a diagnosis of primary microcystic adenoma. Analysis of DNA extracted from sinonasal tumour tissue did not show loss of the wild-type allele at the VHL locus. Although this did not support tumour association with VHL disease, it was not possible to look for a loss-of-function mutation. The association of primary microcystic adenoma of the sinonasal cavity with VHL disease remains speculative. These lesions are benign but are likely to require regular surveillance. Such tumours may require repeated surgical excision.